Aires de Luna Lecturas y Transformaciones de La Cumbia en La Depresión Momposina (2017)
The present project aims to understand the particular view of the origins and transformations of cumbia in the momposina depression and specifically in Banco Magdalena, the municipality in which the national cumbia festival, contributing to the work of evaluation and visibility of this tradition that arises from its inhabitants when interpreting it, feel it and live it as Banqueños and as Colombians.